Effect of propolis extract as a natural preservative on quality and shelf life of marinated chicken breast (chicken Kebab). (1st February 2022) - Mahdavi-Roshan, Marjan; Gheibi, Siamak; Pourfarzad, Amir
Abstract: Propolis extract can be used as a natural preservative in the poultry industry. This study is thus aimed to investigate the effects of propolis aqueous extract on the microbial, physicochemical and sensory characteristics of marinated chicken breast. For this purpose, various contents of the propolis extract (0, 4, 8 and 12% v/w) were employed in the chicken breast marination. The total count, yeasts and molds, Staphylococcus aureus and Escherichia coli, pH, total volatile nitrogen (TVN), texture parameters and sensory specifications of samples were evaluated during 12 days of storage at 5 °C. The growth rate of the microbial population during storage at 5 °C was decreased with the increasing concentration of propolis extract in samples. The sensory analysis showed that the odor changes in the samples containing propolis extract were slower than in the control. In general, samples containing propolis extract presented lower changes in the texture quality parameters throughout the storage time. Principal component analysis (PCA) provided a better understanding of the relationships between underlying features. The partial least squares regression (PLSR) models were applied to find the relationships between instrumental and sensory descriptive data. Highlights: Propolis extract can be recognized as a natural preservative in poultry industry. Using of microbial aspects, sensory evaluation, texture analysis. PCA was used to investigate the marinated chicken breast specialties. PLSR was applied to determine the relationships between sensory and instrumental data.